Development of diffusive drying process using compressed dry air in pharmaceutical industry - Regina Aryanti; Irvan Kartawiria; Paulus Gunawan (Jurnal Teknik Kimia Indonesia, 2013)
Most of drying processes applies excessive heat which damages heat sensitive material, including foods, pharmaceutical, neutraceutical substances, and herbal medicines. Drying approach is categorized into evaporative drying that utilize heat as driving force, and diffusive drying that uses vapor pressure difference to reduce moisture content. Diffusive drying requires media with very low vapor pressure, such as compressed dry air used in pharmaceutical industry. The objective of this research is to develop drying process based on diffusion principle pharmaceutical grade compressed dry air. Process development involves mathematical modeling based on diffusion principles, construction of equipment prototype, validation, and verification of the model using the prototype. Lactose granules (50 g and 70 g) were used as example. The drying process reduces lactose moisture content from 11.38% to 4.75% in 85 seconds at room temperature. Compressed dry air used at moisture content 0.0005% with flow rates of 1.47×10-2, 1.58×10-2, and 1.67×10-2 m3/s (operating pressure of 1.3, 1.6, and 1.8 bars). The diffusive drying model developed in this research has been successfully validated against physical behavior with accuracies of 84.24 - 99.61%. It can be concluded that the compressed dry air in pharmaceutical industry is potential for diffusive drying process at room temperature.Keywords: drying, diffusive, compressed air, model AbstrakKebanyakan proses pengeringan memberikan panas yang berlebihan, yang dapat merusak bahan-bahan peka panas seperti bahan-bahan pangan, farmasetika, nutrasetika, serta obat-obatan herbal. Pendekatan umum proses pengeringan dapat dibedakan menjadi pengeringan evaporatif yang memanfaatkan panas sebagai gaya pendorong, serta pengeringan difusional yang memanfaatkan perbedaan tekanan uap untuk mengurangi kadar air bahan umpan. Pengeringan difusional memerlukan media bertekanan uap sangat rendah untuk melepaskan air dari produk, seperti udara tekan kering, untuk penerapan di industri farmasi. Udara tekan di industri farmasi harus sesuai dengan standar ISO 8573.1 Class 1, yang mensyaratkan kelembaban sangat rendah. Tujuan penelitian ini adalah untuk mengembangkan proses pengeringan berdasarkan prinsip difusi, menggunakan udara tekan kering sesuai standar industri farmasi. Pengembangan melibatkan pemodelan matematik berdasarkan prinsip-prinsip difusi, pembangunan prototipe alat, validasi, dan verifikasi model menggunakan prototipe tersebut. Udara tekan kering memiliki kadar air 0,0005% dengan laju alir divariasikan pada 1.47×10-2 m3/s, 1.58×10-2 m3/s, 1.67×10-2 m3/s (pada tekanan operasi 1,3, 1,6, dan 1,8 bar). Model pengeringan difusional yang dikembangkan berhasil divalidasi terhadap kelakuan nyata dengan akurasi 84.24 - 99.61%. Dapat disimpulkan bahwa udara kering tekan berstandar industri farmasi dapat digunakan untuk proses pengeringan difusional pada temperatur ambien. Kata kunci: pengeringan, difusional, udara tekan, model